KARAMUNTING (Melastoma malabathricum) EXTRACTS ON WHITE SHRIMP (Litopenaeus vannamei) MATURITY - Ahmad Ridwan; Awaludin Awaludin (BIOTROPIA, 2021)
Lanosterol is a phytosterol that is used by crustaceans to form animal steroid hormones that play a role in shrimp reproduction. This research aims to determine the response of ovary development in white shrimp parent after being given karamunting ethanol extract. This research was carried out in several stages: (1) injecting the white shrimp every 3 days at the base of the 5th leg for 15 days with variable control doses of 0 (C), 10 mg/kg BW (T1), 7.5 mg/kg BW (T2), 5 mg/kg BW (T3), 2 mg/kg BW (T4), and 1 mg/kg BW (T5); (2) isolation of white shrimp parent ovary; (3) measurement of progesterone levels in the ovary using the radioimmunoassay (RIA) method; (4) histological observation of white shrimp parent ovary; and (5) data analysis. The statistical results of progesterone level measurements showed that administration of karamunting ethanol extract at the end of maintenance resulted in a significant difference (P < 0.05). Histological observations of gonadal development in the control, T5, and T4 treatments showed that the cells developed into previtellogenic oocytes, whereas in treatments T1, T2, and T3, ovarian cells developed into endogenous vitellogenic oocytes, and only in T1 did ovarian cells develop into exogenous vitellogenic oocytes. Statistical results of oocyte size after administration of karamunting extract at the end of maintenance were significantly different (P < 0.05). The average oocyte size at the beginning of maintenance was 15.57 ± 3.15 μm, while in the control treatment it was 25.29 ± 2.69 μm, indicating that ovarian development occurred at the end of maintenance in both the control and treatment groups. Oocyte sizes in T1 (65.65 ± 2.64 μm), T2 (63.98 ± 3.06 μm), T3 (39.12 ± 6.01 μm), T4 (28.08 ± 0.84 μm), and T5 (27.65 ± 0.71 μm) were also greater than the oocyte size at the beginning of maintenance and in the control. Based on the results of this study, it can be concluded that the lanosterol content in karamunting plants can increase progesterone hormone levels, indicating an acceleration of gonadal maturity and enlargement of oocyte size in white shrimp broodstock.